(untitled) (Research, Society and Development, 2022)
In recent decades, researchers in bone tissue bioengineering have focused on developing and improving bioceramics efficient in presenting physical-chemical characteristics similar to bone tissue, aiming to mimic cellular events and mechanisms involved in osteogenesis. Among the materials used, wollastonite (W) has stood out in recent years, mainly due to its bioactivity. Besides, tricalcium phosphate (TCP) is also used primarily due to its osteoinductivity and osteoconductivity. Given their ionic compositions and the physical-chemical properties of W and TCP, scientists have associated these two materials during the synthesis of bioceramics that unite the characteristics of each material into a single biomaterial, called composite. This design enables a variety of association that allows improvements in the biological behavior of these materials. Therefore, W/TCP composites have shown excellent performance, in vitro and in vivo, as they start to exhibit fundamental properties for bone regeneration. These characteristics indicate the use of these new biomaterials in future clinical applications, especially in cases of extensive bone losses, which remain a significant challenge for scientists and biomedical professionals. Nevertheless, despite the advances achieved, many questions must be clarified, and essential to comprehend the mechanisms involved in osteogenesis after implantation. Thus, this study aimed to contextualize the use of W/TCP composites for bone regeneration, to support further studies necessary to identify the biological behavior of these bioceramics and ensure use in clinical practice.